Rekonstruksi Makna Amal Berkelanjutan dalam Surah Al-Insyirah Ayat 7: Studi Tafsir Al-Mishbah dan Tafsir Al-Azhar - Arif, Muhammad (Nizamiyah: Jurnal Sains, Sosial dan Multidisiplin, 2026)
The phenomenon of the interpretation of Surah al-Inshirah verse 7 has tended to stop at a normative reading that emphasizes the transition from one activity to another without a deeper conceptual exploration of the sustainability of charity in human life. This tendency has implications for an understanding of charity that is temporary, fragmentary, and less integrated with social dynamics and the ethos of sustainability. This paper aims to reconstruct the meaning of sustainable charity in Surah al-Inshirah verse 7 through a study of Nusantara interpretations by examining M. Quraish Shihab’s Tafsir Al-Mishbah and Hamka’s Tafsir Al-Azhar. The approach used is a qualitative one based on literature studies by making both interpretations as the main data sources, while the analysis technique is carried out comparatively critically to identify similarities, differences, and the direction of meaning developed by each interpreter. The results of the study indicate a shift in the meaning of charity from merely a momentary activity of worship or work to the principle of dynamic, progressive, and continuous charity, where each achievement is not understood as an endpoint, but rather as a momentum to give birth to the next, more meaningful charity. The interpretation of al-Mishbah emphasizes the psychological and ethical dimensions of the sustainability of charity, while the interpretation of Al-Azhar emphasizes its correlation with social responsibility and productive work. This reconstruction shows that Surah al-Inshirah verse 7 contains a paradigm of sustainable charity that is relevant to the modern context. Theoretically, this finding enriches the development of the study of Al-Quranic interpretation by strengthening the conceptual framework of sustainable charity as the basis for adaptive and contextual practical ethics.